Isolation of the Etiologic Agent of Human Granulocytic Ehrlichiosis from the White-Footed Mouse (Peromyscus leucopus) - Ravyn, M. Dana (American Society for Microbiology, 2001)
We examined white-footed mice (Peromyscus leucopus) from Minnesota for infection with the etiologic agent of human granulocytic ehrlichiosis (HGE). From April to September 1997, we collected P. leucopus from Washington County, Minnesota, an area enzootic for HGE. Blood was cultivated in HL60 cells for isolation of the HGE agent. Of 59 mice examined, only a single mouse was culture positive for the HGE agent. The 16S ribosomal DNA sequence of the isolate was determined to be identical to that of the HGE agent. The isolate was reactive with monoclonal antibodies to the 44-kDa antigen of the HGE agent and was infectious for laboratory mice.